Fluctuations in Residential Construction: Some Evidence from the Spectral Estimates - Stern, Andrew (The Review of Economics and Statistics, 1972)
to GNP as the CEA had anticipated that it would. As a general conclusion to this brief paper, the following points can be made. The CEA was wrong in stating in its 1963 Report that the tax cut would lessen the sensitivity of income tax revenue to GNP. As a matter of fact, the tax cut of 1964 increased that sensitivity. As a consequence of this increase, the built-in flexibility of the tax declined less than anticipated and would soon recover the before-1964 value. This increase in elasticity would have increased the need for frequent tax reductions if expenditure had continued to increase at the rate that would have been realistic to assume in 1964. The elasticity of the rate structure increased in importance and became almost as important as that of the base. REFERENCES